1984
DOI: 10.1029/ja089ia08p06631
|View full text |Cite
|
Sign up to set email alerts
|

Detailed study of electron plasma waves upstream of the Earth’s bow shock

Abstract: A detailed study of electron plasma waves observed upstream of the earth’s bow shock and of their relationships to the position of the satellite in the foreshock and to the electron measurements has been carried out. The wave characteristics depend on the position in the electron foreshock: a narrow‐band (a few percent) and intense (a few millivolts per meter) noise is observed at the plasma frequency at the edge of the foreshock while the spectrum widens (Δf/f ≃ 0.3) at the same time as the power decreases (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 30 publications
(1 reference statement)
5
96
1
Order By: Relevance
“…Astrophysical examples include Type II and III solar radio bursts (Lin et al 1981(Lin et al , 1986Dulk et al 1984;Goldman 1983;Robinson et al 1993aRobinson et al ,b, 1994Reid & Ratcliffe 2014), outer heliospheric radio emission (Kurth et al 1984), and in planetary electron foreshocks (Etcheto & Faucheux 1984;Moses et al 1984;Fuselier et al 1985;Lacombe et al 1985). Related processes in laboratory plasmas have also been discussed by, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Astrophysical examples include Type II and III solar radio bursts (Lin et al 1981(Lin et al , 1986Dulk et al 1984;Goldman 1983;Robinson et al 1993aRobinson et al ,b, 1994Reid & Ratcliffe 2014), outer heliospheric radio emission (Kurth et al 1984), and in planetary electron foreshocks (Etcheto & Faucheux 1984;Moses et al 1984;Fuselier et al 1985;Lacombe et al 1985). Related processes in laboratory plasmas have also been discussed by, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The wave spectral features and their spatial dependence are described in detail by Etcheto and Faucheux [1984], Fuselief et al [1985], and Lacombe et al [1985]. Narrowband waves (bandwidths of less than a few percent of fpe ) with frequencies near the local plasma frequency fpe (which is typically about 30 kHz, though it varies depending on the solar wind plasma density) are gen- Electromagnetic waves with frequencies of fpeand 2fpehave been observed in regions close to the bow shock and are associated with electrostatic oscillations [Scarf et al, 1970;Dunckel, 1974;Gurnett, 1975 Gary [1985], who showed that when a beam has a sufficiently large density and/or a sufficiently small temperature the Langmuir mode is stable and that a beam mode can be unstable with wave growth occurring at frequencies above the ion plasma frequency.…”
Section: Fitzenreiter Et Al [1990] Developed a 3-d Analyticalmentioning
confidence: 99%
“…Using data from ISEE 1, Etcheto and Faucheux (1984) found that the maximum amplitudes of the Langmuir waves were a few millivolts per meter at the edge of the foreshock and only a few tens to a few hundreds of microvolts per meter inside the foreshock. During a time period when the solar wind magnetic field was unusually constant, used ISEE 1 plasma wave data to show that there is a slight offset of the high wave amplitude region from the boundary of the foreshock.…”
Section: Introductionmentioning
confidence: 99%